The use of social networks in scientific research with questionnaires - Soraya de Mattos Camargo Grossmann; Mariela Dutra Gontijo Moura; Michelle Danielle Porto Matias; Saul Martins Paiva; Ricardo Alves Mesquita (Universidade Estadual de Campinas, 2018)
Aim: The aim of this study was to determine the response rate of the SF-36 quality of life questionnaire sent and received by mail and over a social network to caregivers of individuals with epidermolysis bullosa (EB) in Brazil. Methods: All volunteers were first-degree relatives of patients with EB that directly spent time helping them with their basic activities of daily living. A maximum of two caregivers per patient could answer the questionnaire. Volunteers were divided into two groups: for group 1, questionnaires were sent to 53 members of a support association for the disease by mail, and for group 2, 798 members of the Facebook™ page of friends and relatives of patients with EB were invited to participate using an access link to Google Drive™ to gain access to the questionnaire. The data from both groups were analyzed 150 days after the start the study. Descriptive analysis was performed by EpiInfo8 and the return of questionnaires was evaluated according to age, sex, and time of return using the Chi-squared and Fisher's exact test. Results: After 150 days, 30 questionnaires were returned, 17 (56.7%) of which from group 1 and 13 (43.3%) from group 2. Approximately 12 questionnaires were returned by mail and 11 over the social network. Conclusions: The data collection of the SF-36 quality of life questionnaire from caregivers of individuals with EB over a social network seems to be efficient mainly when it is necessary to collect results within a short timeframe, highlighting the importance of social networks as a means for conducting this type of research. However, in our study, the most efficient method was distributing the questionnaires by mail.